The benefits of utilizing blockchain and big data in the maritime industry - Kougias, Konstantinos; Kalliris, Titios; Kazas, Christos; Hernadez, Elian-Emil (2022)
Digitalization has been recognized as an ongoing process occurring in the maritime sector due to innovating technologies disrupting and changing how business is conducted. This paper aims to develop a comprehensive theoretical overview and practical approach to Blockchain and big data, analyzing the benefits provided by their application in the maritime sector. There are many theoretical applications concerning both innovating technologies that are researched in great detail. Since Blockchain is still in its early stages, it is approached with the perspective of how it can aid the daily challenges of shipping, such as the heavy paper-based documentation. Part of the research is conducted on adopting both technologies in combination, which provides benefits such as efficiency, transparency, safety, and cost reduction. In order to understand the full complexity, the challenges and the possible barriers are explored, such as data issues, governance, and technology integration. Data is drawn from a bibliography overview of theoretical and practical cases analyzing the topic and interviews from maritime professionals with a deep understanding of both technologies, providing input and feedback on the possible application of such technologies and evaluating future opportunities. Conjointly with the interview findings, future opportunities are examined, and many examples are provided, including possible developments in integrating both technologies in the maritime industry.